Mycorrhizal colonization mediated by species interactions in arctic tundra - Urcelay, Roberto Carlos; Bret Harte, M. Syndonia; Díaz, Sandra Myrna; Chapin III, F. Stuart (Oecologia)
The Alaskan tussock tundra is a strongly nutrient-limited ecosystem, where almost all vascular plant species are mycorrhizal. We established a long-term removal experiment to document effects of arctic plant species on ecto- and ericoid mycorrhizal fungi and to investigate whether species interactions and/ or nutrient availability affect mycorrhizal colonization. The treatments applied were removal of Betula nana (Betulaceae, dominant deciduous shrub species), removal of Ledum palustre (Ericaceae, dominant evergreen shrub species), control (no removal), and each of these three treatments with the addition of fertilizer. After 3 years of Ledum removal and fertilization, we found that overall ectomycorrhizal colonization in Betula was significantly reduced. Changes in ectomycorrhizal morphotype composition in removal and fertilized treatments were also observed. These results suggest that the effect of Ledum on Betula's mycorrhizal roots is due to sequestration of nutrients by Ledum, leading to reduced nutrient availability in the soil. In contrast, ericoid mycorrhizal colonization was not affected by fertilization, but the removal of Betula and to a lower degree of Ledum resulted in a reduction of ericoid mycorrhizal colonization suggesting a direct effect of these species on ericoid mycorrhizal colonization. Nutrient availability was only higher in fertilized treatments, but caution should be taken with the interpretation of these data as soil microbes may effectively compete with the ion exchange resins for the nutrients released by plant removal in these nutrient-limited soils. Fil: Urcelay, Roberto Carlos. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - Córdoba. Instituto Multidisciplinario de Biología Vegetal. Universidad Nacional de Córdoba. Facultad de Ciencias Exactas Físicas y Naturales. Instituto Multidisciplinario de Biología Vegetal; Argentina Fil: Bret Harte, M. Syndonia. University Of Alaska; Estados Unidos Fil: Díaz, Sandra Myrna. Consejo ...